Estimation Top and Bottom of Bogor Fault, Kepahiang Regency Based on 2D Magnetotelluric Data Analysis - Muammar, Zaky; Muchammad Farid; Arif Ismul Hadi; Tedy Algozali; Andre Rahmat Al Ansory; Hana Raihana (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Kepahiang Regency, Bengkulu Province, is an area crossed by the Musi segment of the Sumatra Fault and a number of secondary faults, including the Bogor Fault, which contribute to the high level of seismic activity in the region. The presence of these active faults, combined with a relatively high population density, poses a potential threat to infrastructure and public safety. This study aims to identify the subsurface geometric characteristics of the Bogor Fault, particularly its upper and lower depths, as part of earthquake disaster mitigation efforts. The Magnetotelluric (MT) method was used in this survey with the ADU-07e system, which utilizes natural electromagnetic fields, with two horizontal electrical sensors (Ex, Ey) and three horizontal sensors (Hx, Hy), as well as a vertical magnetic sensor (Hz). Data collection was conducted at six measurement points with a 1 km interval along the Northeast–Southwest transect that crosses the Musi Fault and the Bogor Fault. Data processing was performed using MAPROS software for time-domain to frequency-domain conversion, and ZONDMT2D for subsurface modeling. The modeling results showed a low resistivity zone at point T6, with values between 0.21–1.6 Ωm, which was interpreted as the presence of the Bogor Fault. This zone was identified at a depth of approximately 2 km and was estimated to extend more than 8 km in the north–south direction. This finding provides important indications of the presence of an active fault in the area and can serve as a basis for earthquake risk mitigation efforts in Kepahiang.